2017
DOI: 10.21276/aimdr.2017.3.5.me3
|View full text |Cite
|
Sign up to set email alerts
|

ECG and ECHO Changes in CKD

Abstract: Background: Cardiovascular causes contribute towards the large proportion of increased morbidity and mortality,in patients ofChronic renal failure. Cardiac disease is the major cause of death in dialysis population. Methods: The present study was undertaken for documentation of various cardiovascular abnormalities in sixty patients with Chronic Kidney Disease at Government Medical College Patiala, using Electrocardiography and Echocardiography as investigation procedures.The present study is a descriptive -cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
1
3
1
Order By: Relevance
“…Our study showed that abnormal ECGs were found in 92.1% of all CKD patients. This is higher than previous studies, where abnormal ECG measurements were found in 50-86% of all patients [4,6,11,13,14]. In this study, prolonged QTc interval was the most common ECG finding observed.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Our study showed that abnormal ECGs were found in 92.1% of all CKD patients. This is higher than previous studies, where abnormal ECG measurements were found in 50-86% of all patients [4,6,11,13,14]. In this study, prolonged QTc interval was the most common ECG finding observed.…”
Section: Discussioncontrasting
confidence: 68%
“…Furthermore, previous research by Rodriguez et al showed that the QRS frontal axis was more leftward in the population with significant microalbuminuria [32]. Sachdeva et al also showed left axis deviation in 15% of their CKD patients [14]. Our study showed the frequency of frontal axis deviation was found in 11% CKD patients without further investigation of the microalbuminuria status.…”
Section: Discussionsupporting
confidence: 53%
“…Comparison of twodimensional echocardiographic changes in CKD cases with other studiesParticularsRamanan et al12 Laddha et al13 Goornavar et al14 Singal et al15 Sachdeva et al16 Present study(2017) …”
mentioning
confidence: 70%
“…Similarly, Sachdeva et al concluded that based on echocardiographic changes, LVDD was present in 38.33% patients, Krishna et al reported LVDD in 38%, Ladha et al reported LVDD in 61.4% and Singal et al reported in 50%. [22][23][24][25] Rao et al found that 67.2% of subjects had diastolic dysfunction. 26 Losi et al in a cross-sectional study declare that nearly 40% of the patients had diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%